Quantum phase constraints as the origin of zero-field splitting: the case of [Ni(Me6tren)Cl](ClO4) - Miroslav Georgiev; Hassan Chamati (Scientific Reports)
Abstract Conducting a thorough theoretical study of the magnetic properties of the spin-one [Ni(Me6tren)Cl](ClO4) complex, the present paper unveils the most probable quantum effect underlying the seemingly unusual magnetic behavior of Nickel based complexes exhibiting trigonal (bi-)pyramidal coordination geometry. The study unequivocally shows that the constrained orbital motion of the valence electrons is a primordial quantum effect underlying the rise of a fine structure in the energy spectrum of these molecule magnets and consequently shapes their magnetic behavior. Furthermore, it reveals the ostensible nature of the huge zero-field splitting and points out to the most probable reason to the emergence of such a notion. Accordingly, the probed experimental magnetic properties of the studied complex reported in the literature are reproduced only after the implementation of phase constraints. The conventional approach accounting for the valence electrons as unconstrained does not fit to the experimental findings. The devised method can be applied to study the magnetic properties of all molecule magnets based on metal ions with highly filled valence subshell, including the polynuclear ones.